1997
DOI: 10.2323/jgam.43.133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of six species of white-rot basidiomycetes on the chemical composition and rumen degradability of wheat straw.

Abstract: This study was conducted to investigate changes in in vitro dry matter digestibility (IVDMD), volatile fatty acids (VFA) production and cell-wall constituent degradation in wheat straw treated with six white-rot fungi: Daedalea quercina, Hericium clathroides, Phelinus laevigatus, lnonotus andersonii, lnonotus obliquus, and lnonotus dryophilus. The incubation of wheat straw for 30 days at 28°C improved IVDMD from 41.4 (control) to 59.2% for D. quercina, 56.3% for H. clathroides, 50.2% for P. laevigatus, 51.4% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
4
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 11 publications
1
7
4
1
Order By: Relevance
“…An increasing of DMD of wheat straw fermented with Pleurotus fungi has been reported from 15 to 46% (Zadrazil, 1997). Beside the culturing conditions, the ability of various strains of white-rot fungi in cell wall degradation and digestibility improvement of straw may be different (Tripathi and Yadav, 1992;Jalc et al, 1997;Fazaeli et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing of DMD of wheat straw fermented with Pleurotus fungi has been reported from 15 to 46% (Zadrazil, 1997). Beside the culturing conditions, the ability of various strains of white-rot fungi in cell wall degradation and digestibility improvement of straw may be different (Tripathi and Yadav, 1992;Jalc et al, 1997;Fazaeli et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The bio-conversion of straw is circumscribed to the group of white-rot fungi, which are capable to colonize on cereal straw and liberate water soluble substrates from the polymers during SSF and thus improve the digestibility (Zadrazil, 1997;Fazaeli et al, 2003). Among the edible white-rot fungi, the Pleurotus species have been shown to be more efficient (Zadrazil et al, 1996;Jalc et al, 1997;Taniguchi et al, 2005). The potential of Pleurotus fungi such as P. ostreatus and P. eryngii to reduce indigestible cell wall components and increase the dry mater digestibility (DMD) of straw has been reported (Singh et al, 1990;Fazaeli et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Nutritive value of cereals straw cultured with pleurotus fungi has been reported by some researcher (Dehanda et al,1996;Zadrazil,1997;Jalc et al .,1997 andfazaeli et al .,2004). Khorshed,(2000) reported that biological treatment (T.viridi,S.cerevisae or T.viridi+S.cerevisae)decreased significantly (P<0.05)DM,OM,CF and NFE(P<0.01) and increased the contant of ash and CP for wheat straw.He also found that NDF, cellulose and ADF contents decreased (P<0.01).…”
Section: Introductionmentioning
confidence: 73%
“…The present findings like that of the effect of white rot fungi on the biodegradation of tannins in sericea lespedeza (Gamble et al, 1996) and the digestion enhancement of wheat straw (Jalc et al, 1997) are of a preliminary nature. Further work is warranted to explore the possibility of exploiting the detannification potential of this fungal strain for pilot and large-scale applications, coupled with isolating the strains of A. niger capable of preferentially degrading tannins with a minimum loss of dry matter and digestible material.…”
mentioning
confidence: 80%